Morbidity and mortality from technological disasters in Iran: A narrative review - Hamid Jafari; Ahmad Jonidi Jafari; Mahmoud Nekoei-Moghadam; Salime Goharinezhad (Wolters Kluwer Medknow Publications, 2019)
Iran as a developing country is at risk of vulnerability to technological disasters. These types of disasters occur frequently in last years and affected thousands of lives. Technological disasters in Iran cause thousands of deaths, thousands of injuries, and millions of dollars' economic loss in recent years. We searched suitable keywords in national and international disaster databases for gathering epidemiological data in these disasters in Iran. In addition, we searched suitable keywords in scientific databases including Google Scholar, Scopus, PubMed, Web of Knowledge, Scientific Information Database, Magiran, and Irandoc. After screening, only 19 articles discussed challenges of technological disasters in the country. Road accidents, explosions and fires, mine accidents, and railway accidents are common events in the country. After 2015, these types of disaster cause 823 deaths and injuries. Experience of response to these disasters showed that technological disaster management in the country faces too many challenges including comprehensive and prospective programs, weakness of necessary infrastructure for urban management, weakness in group work and interorganizational coordination, lack of coherent involvement of people and nongovernmental organizations, lack of information coverage during the disaster, volunteers in police service presence at scene, and normalization of these events. Due to interorganizational nature of mitigation in technological disasters, it must be developed coordination between various organizations to mitigate these types of disasters.